Analysis on the Structure and Purposes of Travel Blog Posts - Juliaty, Hanna; Dita, Agustina (Universitas Negeri Semarang, 2021)
Travel blogs have become a huge online platform used as a benchmark for Internet users to plan holiday itineraries, consider choices, and finalize travel-related purchase decisions. As popular travel blogs are often visited by online readers globally, there might be a shift in the purposes for writing travel blogs nowadays compared to traditional blog posts. Previous studies discussed the characteristics of blogs as a communicative platform; however, discussion on language features and blog structures used to achieve certain purposes of travel blogs is still scarce. This study, hence, aimed to evaluate the text structure and language function employed in popular travel blogs to determine their overall purposes. Eighteen posts were selected from six popular travel blogs and analyzed qualitatively by using Pascual’s (2018) blog structure moves and Jakobson’s (1960) language function framework. The findings showed that the travel blog posts consisted of four moves: situational, descriptive, closure, and invitational moves and that most of the moves mainly employed referential and emotive functions. Hence, the main purposes were to provide information on travel destinations and to express the bloggers’ feelings towards their travel experiences. The findings implied that the purposes of popular travel blog posts nowadays are related to the role of blogs as a source of information and the role of travel bloggers as social influencers in the online community.